Governance Impact on Private Investment: Evidence from the International Patterns of Infrastructure Bond Risk Pricing - Nina B. Bubnova

(untitled)
During the last decade, infrastructure finance and provision graduated from traditional means to more innovative ones, primarily initiated by private companies and supported through their equity and debt. Capital markets increasingly became the main funding source for infrastructure projects worldwide, including investments in developing and transition countries where infrastructure penetration still falls considerably short of needs. Infrastructure bonds served as the most popular method of oil, gas, electricity, telecommunications, and transport project financing in these countries throughout 1990–99, thereby substituting government funding. Thriving markets require not only an appropriately designed economic system, but also a secure political foundation that limits the ability of the state to confiscate wealth. This requires a presence of political institutions that credibly commit the state to honor economic and political rights. Investments in infrastructure are particularly susceptible to the risks of government interference. Constructive government noninvolvement—necessary regulation excepted—is likely to fail in societies that lack the institutions to serve as checks and balances on government action, as well as in those societies that do not possess a longstanding tradition of law and order. These and other risks impinge on investor confidence, an effect exacerbated by the recent global financial crisis. The need to boost private capital flow to infrastructure projects requires policy measures that will reduce investor perceptions of the risk of default due to adverse government action. This paper uses international cross-sectional and time-series infrastructure bond risk premium and credit rating history data from the past decade to examine the factors that influence investor risk perceptions and that inflate the cost of borrowing for essential infrastructure. The information thus generated about key governance risks is then analyzed for its policy implications.